Age and education moderate the relationship between confidence in health and political authorities and intention to adopt COVID-19 health-protective behaviours. Issue 9 (25th February 2021) - Mata, Fernanda; Martins, Pedro S.R.; Lopes-Silva, Julia B.; Mansur-Alves, Marcela; Saeri, Alexander; Grundy, Emily; Slattery, Peter; Smith, Liam
Abstract : Purpose: This study aimed to examine (1) whether confidence in political and health authorities predicted intention to adopt recommended health-protective behaviours and (2) whether age, gender and education level moderated the relationship between confidence in political and health authorities and health protective-behaviours (download the COVIDSafe app, wear a face mask and stay at home). Design/methodology/approach: This study assessed 1, 206 Australians using an online survey. Participants answered questions regarding their confidence in political and health authorities and intention to adopt health-protective measures. Findings: Confidence in health and political authorities predicted intention to stay home and intention to download the COVIDSafe app, but not to wear a face mask in public spaces. Age moderated the relationship between confidence in authorities and intention to stay home (i.e. among respondents with less than 54 years old, confidence in authorities was associated with higher intention to stay home). Further, age and education level moderated the relationship between confidence in authorities and intention to download the COVIDSafe app (i.e. among older respondents and those with a university degree or higher, confidence in authorities was more strongly associated with higher intention to download the COVIDSafe app). The interaction between confidence and education predicted adoption of mask-wearing (i.e. among participants with a university degree or higher, more confidence in authorities was associated with higher intention to wear a mask in public spaces). Originality/value: Our findings can inform the development of targeted communications to increase health-protective behaviours at early stages of future pandemics.